Perception of Administrative Corruption Among Business Managers in Baghdad, Iraq. - Faaeq, Munadil K. (2007)
This study is an attempt to examine the perception of administrative corruption among managers of business organizations in Baghdad, Iraq. A survey was camed out among 16 business managers in the area of Resafa in Baghdad .The result of the survey showed that the mangers are aware about the incident of corruptions. In addition the managers also suggest some measures to reduce corruption in Iraq.